The role of serum albumin in the prediction of malnutrition in patients at least five yr after heart transplantation. (10th May 2014) - Prenner, Günther; Wasler, Andrä; Fahrleinter‐Pammer, Astrid; Werkgartner, Georg; Mischinger, Hans Jörg; Koter, Stephan; Roller, Regina; Wagner, Doris
Abstract Objectives Malnutrition after heart transplantation (HTX) is related to graft sclerosis. The risk for malnutrition is often underestimated by conventional measurements. We aimed to compare these with objective assessors for malnutrition. Methods Recipients at least five yr after HTX were included. Body mass index (BMI), bioimpedance analysis (BIA), serum albumin (SA) and subjective global assessment (SGA) malnutrition, and concomitant diseases were assessed. The BIA was used as gold standard, and a phase difference (PD) <4 was defined as cutoff. Results Sixty recipients (47 male, 13 female) were analyzed. The prevalence of malnutrition was according to SGA 6.6% (4/60), BMI 8.3% (5/60), SA 31.6% (19/60), and BIA 48.3% (19/60). PD values did not correlate with BMI (r = 0.118; p = 0.079) or SGA (r = 0.289; p = 0.65), but with SA (r = 0.458; p = 0.001). Multivariate analysis yield SA and sCr as independent predictors for an existing malnutrition. ROC analysis showed an area under the receiver operating characteristic curve of 0.606 for SA as compared to 0.515 for the BMI and 0.698 for sCr in the prediction of existing malnutrition as defined by the PD. Conclusion The BMI or the SGA did not show as much power in predicting an existing alimentary deficiency for heart recipients as did SA.